Kedudukan Anak Tiri Dalam Pembagian Harta Warisan di Desa Kualalumpur Kec Paguyaman - Sri Susanti Auna; Mutia Ch. Thalib; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out the legal rules regarding the parentage of stepchildren in the distribution of inheritance according to the Civil Code and the Compilation of Islamic Law and to find out the legal consequences of having stepchildren inherit from their stepparents in Kualalumpur Village, Kec. Paguyaman. This research uses the Normative/Empirical Juridical type of research. The results of this research found that the position of stepchildren in inheritance distribution according to the Civil Code and KHI is that stepchildren are not classified as heirs of their stepparents, stepchildren can only inherit from their biological parents even if they were brought to their biological parents' most recent marriage. Under Islamic law, stepchildren can inherit their stepparents' inheritance by means of a will. The Impact of Position Law on Stepchildren Inheriting From Their Stepparents in Kuala Lumpur Village, District. Paguyaman is: Stepchildren do not inherit from their stepparents, stepchildren become an obstacle which results in a reduction in their stepparent's share, stepchildren can only be given a compulsory will.